2014
DOI: 10.1039/c4lc00505h
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic approach for investigating multicomponent system thermodynamics at high pressures and temperatures

Abstract: In this work, we present a novel microfluidic-based approach for investigating the thermodynamics of multicomponent systems at high pressures and temperatures, such as determining miscibility diagrams and critical coordinates of complex mixtures. The developed method is primarily based on (i) bubble and dew point detection through optical characterization and (ii) the use of a so-called dynamic stop-flow measurement mode for fast screening of the diagram parameters, mainly P, T and composition. Our strategy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…Recently, specialized microfluidic approaches have been applied to measure isolated phase properties, including the dew point, bubble point, and liquid‐to‐vapor ratios . These methods each use direct visual observation to determine the formation of droplets or bubbles within a confined planar surface or microfluidic channel and benefit from short equilibrium times, reduced sample volume requirements and precise control over pressure and temperature offered by microfluidic systems .…”
Section: Figurementioning
confidence: 99%
“…Recently, specialized microfluidic approaches have been applied to measure isolated phase properties, including the dew point, bubble point, and liquid‐to‐vapor ratios . These methods each use direct visual observation to determine the formation of droplets or bubbles within a confined planar surface or microfluidic channel and benefit from short equilibrium times, reduced sample volume requirements and precise control over pressure and temperature offered by microfluidic systems .…”
Section: Figurementioning
confidence: 99%
“…Before studying APR with a similar configuration, we first aim to evaluate the phase transition of model APR reaction mixtures. A number of microfluidic set-ups have specifically been described for studying phase transitions and for degassing processes [14][15][16][17][18][19]. Some microfluidic devices contain a constriction in the microchannel, behind which vortices are created.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Marre et al have demonstrated how a simple glass/silicon chip can be used for many applications, e.g. a pressure-volumetemperature cell for scCO 2 [8], quantum dot synthesis using supercritical hexane [9], and supercritical water oxidation [10].…”
Section: Page 3 Of 30mentioning
confidence: 99%